The morphological and biological characteristics of a virulent PI phage isolated from slaughterhouse sewage in Shiraz, Iran - Sepideh Khalatbari-Limaki; Saeid Hosseinzadeh; Seyed Shahram Shekarforoush; Enayat Berizi (Iranian Journal of Microbiology, 2020)
Background and Objectives: Foodborne pathogens are among the serious problems all around the world and thus a novel and natural strategy to control and to inhibit such pathogens is highly demanded nowadays. The aim of this study was to isolate a specific bacteriophage of Escherichia coli O157:H7 from sewage in Fars province, Iran to determine its morphological and antimicrobial activities. Materials and Methods: In order to isolate the bacteriophage of E. coli O157:H7, 10 samples of slaughterhouse wastewaters were used. Double-Layer Agar method was employed to isolate the bacteriophage. To identify the fine structure of the bacteriophage, electron microscope was employed. Host range and antibacterial activity of the phage was also investigated, in vitro. Results: The morphological and biological characteristics of a virulent Siphoviridae phage, PI, are reported. It was found that infection of E. coli O157:H7 strains with this specific bacteriophage produce clear plaques. In the one-step growth analysis, it was confirmed that the phage has been characterized with a very short rise period (around 15 min), an average burst size of 193 PFU/cell, high infectivity and potent lytic action. The bacteriolytic activity of PI was also investigated, in vitro. It was also clarified that at the MOI of 100, 10 and 1, the phage rapidly lysed the bacterial cells within 0.5 or 2 h. Conclusion: These results indicate that the phage PI is a newly discovered phage against E. coli O157:H7 in Iran which may be recommended to use as bio-control purposes.